2016
DOI: 10.1111/hae.12963
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pegylated full‐length recombinant factor VIII with extended half‐life for perioperative haemostasis in haemophilia A patients

Abstract: Introduction: BAX 855 is a pegylated full-length recombinant factor VIII (rFVIII) with an extended half-life, built on a licensed rFVIII (ADVATE â ). BAX 855 demonstrated efficacy and safety in prophylaxis and the treatment of bleeding episodes in previously treated patients (PTPs) with severe haemophilia A. Aim: This phase 3 surgery study evaluates the haemostatic efficacy and safety of BAX 855 for perioperative haemostasis in PTPs with severe haemophilia A undergoing surgery. Methods: Elective procedures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 25 publications
6
29
0
Order By: Relevance
“…A phase III surgical study with BAX 855 (NCT01913405) initiated in December 2013 is currently ongoing and an interim analysis has been recently published [19]. This first analysis reports on 15 procedures (11 major) in 15 subjects for which overall intra- and peri-operative haemostatic efficacy was rated as “excellent” in all cases and no related adverse events were observed [19].…”
Section: Extended Half-life Fviii Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase III surgical study with BAX 855 (NCT01913405) initiated in December 2013 is currently ongoing and an interim analysis has been recently published [19]. This first analysis reports on 15 procedures (11 major) in 15 subjects for which overall intra- and peri-operative haemostatic efficacy was rated as “excellent” in all cases and no related adverse events were observed [19].…”
Section: Extended Half-life Fviii Productsmentioning
confidence: 99%
“…This first analysis reports on 15 procedures (11 major) in 15 subjects for which overall intra- and peri-operative haemostatic efficacy was rated as “excellent” in all cases and no related adverse events were observed [19]. Surgical procedures were covered on average with 30–35 IU/kg twice daily maintaining a mean trough level well above 50% until post-operative Day 7 [19]. …”
Section: Extended Half-life Fviii Productsmentioning
confidence: 99%
“…Furthermore, it was shown that BAX855 is safe and hemostatically effective in patients with severe hemophilia A undergoing surgery [32].…”
Section: Fviii Products (mentioning
confidence: 99%
“…Moreover, the enhanced affinity for VWF may accelerate the formation of VWF:FVIII complex that not only increases the half-life but also may result in decreased immunogenicity by inhibiting endocytosis of FVIII by dendritic cells 25,26. These modifications resulted in a FVIII molecule with an increased half-life that is comparable to the PEGylated EHL product (Adynovate) 8,10,27,28. When FVIII is normally activated, the heavy and light chains are cleaved and released from VWF.…”
Section: Current Factors Available and Extended Half-life (Ehl) Factomentioning
confidence: 99%